Influence of Machine Parameters and Coagulant on the Textural Properties of Paneer (Indian Cottage Cheese) - S. Sivaranjani; N. Karpoora Sundara Pandian; S. Parveen; D. Baskaran; V. Arun Prasath; V. Eyarkai Nambi; R. Pandiselvam (Journal of Food Quality)
Paneer is an acid coagulated concentrated indigenous Indian dairy product. The texture of paneer manufactured from a developed automatic machine was studied with respect to the processing parameters such as coagulation temperature (70–90°C), pressure (0.3–0.6 MPa), types of coagulant (vinegar and citric acid), and milk (cow, buffalo, and full cream milk). The paneer samples were analysed for texture profile analysis of hardness, adhesiveness, springiness, gumminess, chewiness, and cohesiveness. An inscribed central composite design was used to optimize the desired textural characteristics of paneer such as minimum hardness and maximum springiness of paneer. The optimization result concluded that the full cream milk at the coagulation temperature of 88°C with citric acid at pneumatic pressure of 0.3 MPa would result on minimum hardness of 105.84 N and the springiness value of 0.6073, and the result was validated.